Macroporous perovskite nanocrystal composites for ultrasensitive copper ion detection. Issue 33 (28th July 2022) - Li, Hanchen; Yin, Wenping; Ng, Chun Kiu; Huang, Ruoxi; Du, Shengrong; Sharma, Manoj; Li, Bin; Yuan, Gangcheng; Michalska, Monika; Matta, Sri Kasi; Chen, Yu; Chandrasekaran, Naresh; et al.
Abstract : CsPbBr3 -(SH)polyHIPE composite was produced by adhering CsPbBr3 nanocrystals to a (SH)-polyHIPE substrate. This well-designed composite has an extremely high sensitivity to copper ions in organic solvents. Abstract : Accumulation of heavy metal ions, including copper ions (Cu 2+ ), presents a serious threat to human health and to the environment. A substantial amount of research has focused on detecting such species in aqueous solutions. However, progress towards ultrasensitive and easy-to-use sensors for non-aqueous solutions is still limited. Here, we focus on the detection of copper species in hexane, realising ultra-sensitive detection through a fluorescence-based approach. To achieve this, a novel macroporous composite material has been developed featuring luminescent CsPbBr3 nanocrystals (NCs) chemically adhered to a polymerized high internal phase emulsion (polyHIPE) substrate through surface thiol groups. Due to this thiol functionality, sub-monolayer NC formation is realised, which also renders outstanding stability of the composite in the ambient environment. Copper detection is achieved through a direct solution based immersion of the CsPbBr3 -(SH)polyHIPE composite, which results in concentration-dependent quenching of the NC photoluminescence. This newly developed sensor has a limit of detection (LOD) for copper as low as 1 × 10 −16 M, and a wide operating window spanning 10 −2 to 10 −16 M. Moreover, the composite exhibits excellent selectivity among different transition metals.